In the Field: Visiting Peer Institutions to Inform Pediatric Palliative Care Program Redevelopment - Cleveland, Ross W.; Heneghan, Chelsea; Gouda, Suzanne; Liaw, Shih-Ning; Murphy, Terrance; Battista, Vanessa; Frechette, Eleanor; Larocque, Carlie; Rosenberg, Abby R. (Journal of pain and symptom management, 2025)
The heterogeneity of pediatric palliative care (PPC) programs presents challenges in forming a generalized model for growth. We developed and implemented a system to visit and learn from peer institutions to inform our own program’s revision and expansion. To describe the use of structured field trips to peer programs in North America to inform program development. Our procedure involved three steps: First, “organization” included choosing visit sites, outreach and collaboration to plan logistics, development of a standardized approach, and creating inter-disciplinary field trip teams to ensure diverse PPC perspectives during each visit. Second, “conduction” included the field trips, creating a semi-structured debriefing interview guide aimed at uncovering common tensions, and performing interviews with those who went on each trip. Third, “application” involved analyzing interview data to identify and name key tensions, sharing those tension points with the team, and centering those points in a clinical model redesign. We completed 7 field trips, including 16 interdisciplinary members of our team. Analysis of our debriefing interviews yielded 2 primary and 5 sub-themes/tension points. Focusing on recognizing, accepting, mitigating, or eliminating those tension points during a clinical model redesign led to the creation of several formative changes to our team structure. The field trips took 8 months from beginning to delivery of a new clinical model. Field trips to peer PPC teams highlight both shared and unique strengths and challenges PPC teams experience. Knowledge gained from trips may enable creative and informed guidance of PPC programmatic growth and evolution.